Clinical and tomographic characteristics of patients with ischemic cerebrovascular disease - Raciel Alejandro Ruiz Mariño; Martha Campos Muñoz; Daniela de la Caridad Rodríguez Campos; Osmel Daniel Chacón Reyes (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The clinical method by itself is not definitive to diagnose a cerebrovascular disease, reason why the use of imaging diagnostic means, as the computerized axial tomography is important, as it allows to investigate the morphological and functional aspects of the brain.  Objective: To describe the clinical and tomographic characteristics of patients with complete stroke.  Methods: A descriptive and cross-sectional study of 269 patients with complete stroke, assisted in Saturnino Lora Torres Teaching Clinical Surgical Provincial Hospital was carried out in Santiago de Cuba, from January to December, 2019.   Results: There was a prevalence of the male sex (54.6 %), 70-79 age group, motor disorders (76.5 %), alteration of the conscience (51.3 %) and language disorder (50.5 %). In 38 patients the results of the tomography were negative before the 24 hours of clinical course and 64.0 % were better with aftereffects of the disease.   Conclusions: Tomography before the 24 hours demonstrates a low positivity and findings have a favorable clinical course as time goes by, although it is possible to recognize several early signs of acute ictus in less than 4-6 hours.